2021
DOI: 10.1186/s12951-021-01067-0
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized nanoparticles with monocyte membranes and rapamycin achieve synergistic chemoimmunotherapy for reperfusion-induced injury in ischemic stroke

Abstract: Background Ischemic stroke is an acute and severe neurological disease, and reperfusion is an effective way to reverse brain damage after stroke. However, reperfusion causes secondary tissue damage induced by inflammatory responses, called ischemia/reperfusion (I/R) injury. Current therapeutic strategies that control inflammation to treat I/R are less than satisfactory. Results We report a kind of shield and sword nano-soldier functionalized nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 53 publications
0
37
0
Order By: Relevance
“…Besides, McM/RNPs can actively target and bind to inflammatory ECs, thus can serve as a shield between monocytes and ECs. 426 It has been revealed that resolvin D2 exhibited a critical role in the modulation of inflammation and tissue repair. Membrane-derived nanovesicles-encapsulated resolvin D2 pronouncedly enhanced its therapeutic efficacy in treating murine ischemic stroke.…”
Section: Nanoparticle-based Therapeutic Methods For Vascular Aging-re...mentioning
confidence: 99%
“…Besides, McM/RNPs can actively target and bind to inflammatory ECs, thus can serve as a shield between monocytes and ECs. 426 It has been revealed that resolvin D2 exhibited a critical role in the modulation of inflammation and tissue repair. Membrane-derived nanovesicles-encapsulated resolvin D2 pronouncedly enhanced its therapeutic efficacy in treating murine ischemic stroke.…”
Section: Nanoparticle-based Therapeutic Methods For Vascular Aging-re...mentioning
confidence: 99%
“…Immunosuppressants are also the preferred candidates to modulate inflammation after IS ( Qiu et al, 2021 ); for example, mTOR inhibitor rapamycin (RNP) is a potent immunosuppressive agent with anti-inflammatory and anti-proliferative effects ( Querfurth and Lee, 2021 ). Monocytes membrane-coated RNP exerts chemo immunotherapeutic effects with high biosafety by retarding monocyte adhesion to endothelial cells and the recruitment of monocytes ( Wang et al, 2021d ). In another pathway, decreasing neutrophil infiltration by interfering with the interplay between neutrophil and endothelial cells blocks the inflammatory cascade triggered by the recruitment of peripheral inflammatory cells ( Planas, 2018 ; Jian et al, 2019 ).…”
Section: Neurorestorative and Neuroprotective Mechanism Of Biomaterialsmentioning
confidence: 99%
“…The results obtained from the in vivo and in vitro experiments showed that the formulation prepared achieved binding to the inflammatory epithelial cells to inhibit the proliferation of inflammation in the injury site. Thus, the particle contributed immunotherapy against the ischemic stroke-induced rat model, and also enhanced the regeneration [ 15 ]. Macrophages are specialized innate immune cells responsible for maintaining the physiological ambiance.…”
Section: Cell Membrane-coated Nanocarrier Systemmentioning
confidence: 99%